Notifiche
Cancella tutti

Integrali indefiniti.

  

1
315

Spiegare i passaggi.

Autore
1 Risposta



2

Puliamo l'esponente dell'esponenziale per semplificare i calcoli del metodo per parti.

Poniamo $ x = -2t \; ⇒ \; t = -\frac{1}{2}x \; ⇒ \; -\frac{1}{2} dx = dt $

Per parti

  • fattore finito $f(x) = x \; ⇒\; f'(x) = 1$
  • fattore differ. $g'(x) = e^x \; ⇒ \; g(x) = e^x $

 

$ \int -\frac{1}{2x} x e^x (-\frac{1}{2}) \, dx = \frac{1}{4} \int x e^x dx = \frac{1}{4} xe^x -  \frac{1}{4} \int e^x dx =  \frac{1}{4} xe^x -  \frac{1}{4} e^x +c = -\frac{1}{4} 2te^{-2t
} -  \frac{1}{4} e^{-2t} +c = -\frac{1}{4}(2t + 1)e^{-2t} + c $



Risposta
SOS Matematica

4.6
SCARICA